The use of Computer in Accounting Courses - Bengharbin, salem (Dirasat in Economics and Business, 1984)
The purpose of this article vnih published in the Arabic section of this issue is towfold; First, to review related literature concerning the using of computer assisted instructio. Second, to Suggest some "pplication of computer in the Accounting courses in our school. Some suggestions - concering the puter applications in Accounting courscz — are discussed by the article.